Plays one - Eccleshare, Thomas (Modern playwrights., 2019)
"Collected together for the first time are four works by young British playwright Thomas Eccleshare, whose plays have been performed to national and international acclaim over the past decade. This collection includes Pastoral (winner of the Verity Bargate Award 2011), I'm Not Here Right Now, Heather and Instructions for Correct Assembly, Eccleshare's most recent play, which premiered Downstairs at the Royal Court in 2018. Boldly theatrical and formally daring, these plays interrogate the modern world with poetry, poignancy and humour. Exploring themes such as love, imagination and the power of stories, this collection presents one of the bright new writing talents in UK theatre."--Back cover.